Diversidad de los hábitats submareales de la Península de Santa Elena e Islas Murciélago, Pacífico Norte, Costa Rica - Fernández García, Cindy (2021)
Introduction: Worldwide, coastal habitats are experiencing increasing pressure from pollution, coastal development, fisheries, and climate change. Identifying and recording coastal biodiversity is essential to assess ecosystems’ health, changes and the extent of biodiversity loss. Coastal tropical habitats such as coral reefs and seagrass beds have been the research focus for scientists during the last decades; however, other ecosystems have been neglected, such as macroalgae forests, subtidal (20-30 m deep) sedimentary bottoms, and rocky reefs. Objective: Our study reports the marine biodiversity associated with rocky reefs, coral reefs, Sargassum forests and sedimentary subtidal bottoms (20-30 m deep), in a tropical seasonal upwelling area (Santa Elena Peninsula, Santa Elena Bay, and Murciélago Islands, Costa Rica). Methods: During the ‘Santa Elena Expedition’ (April 21-May 2 2018), a total of 28 sites were visited in order to record the biodiversity across four different habitats (rocky and coral reefs, Sargassum forests, subtidal sedimentary bottoms), using SCUBA and both systematic surveys and visual assessments; in some sedimentary bottoms a 20-minute dredge tows were done. Results: A total of 254 taxa were identified, being bony fishes the most diverse group (91 species), followed by gastropods (25 spp.), red algae (21 spp.) and anthozoans (19 spp.). We report four new records for the Pacific mainland of Costa Rica, including the subclass of tube-dwelling sea anemone (Ceriantharia). Conclusions: Our results show that Santa Elena Peninsula, Santa Elena Bay, and Murciélago Islands harbor uncommon and unstudied habitats, such as Sargassum forests, sedimentary bottoms, reefs constructed by the stony coral Pavona gigantea –which is very unusual– and rocky reef communities dominated by calcareous colonies of polychaetes (Salmacina tribranchiata).